Automatic power factor correction using a harmonic-suppressed TCR equipped with a new adaptive current controller - Obais A.M.; Pasupuleti J. (Korean Institute of Power Electronics, 2023)
In this paper, a new continuously and linearly controlled capacitive static VAR compensator is proposed for the automatic power factor correction of inductive single phase loads in 220V 50Hz power system networks. The compensator is constructed of a harmonic-suppressed TCR equipped with a new adaptive current controller. The harmonic-suppressed TCR is a new configuration that includes a thyristor controlled reactor (TCR) shunted by a passive third harmonic filter. In addition, the parallel configuration is connected to an AC source via a series first harmonic filter. The harmonic-suppressed TCR is designed so that negligible harmonic current components are injected into the AC source. The compensator is equipped with a new adaptive closed loop current controller, which responds linearly to reactive current demands. The no load operating losses of this compensator are negligible when compared to its capacitive reactive current rating. The proposed system is validated on PSpice which is very close in terms of performance to real hardware. © 2014 KIPE.